An analysis of swimmer's passive wave resistance using experimental data and CFD simulations - Banks, J.; James, M.; Hudson, D.; Taunton, D.; Turnock, S. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The passive resistance of a swimmer on the free surface has previously been researched experimentally. The contribution of wave resistance to total drag for a swimmer with a velocity around 2.0 m.s- 1 was found to vary from 5% for Vorontsov and Rumyantsev (2000), to 21% for Toussaint et al. (2002) and up to 60% according to Vennell et al. (2006). The exact resistance breakdown of a swimmer remains unknown due to difficulties in the direct measurement of wave resistance. As noted by Sato and Hino (2010), this lack of experimental data makes it difficult to validate numerical simulations of swimmers on the free surface. This study is therefore aimed at presenting direct measurements of a swimmer's total drag and wave resistance, along with the longitudinal wave cuts which may be used to validate numerical simulations. In this paper, experimental data of a swimmer's resistance are presented at two different velocities (case 1 = 1.7 m/s and case 2 = 2.1 m/s ). Total drag was measured using force block dynamometers mounted on a custom-built tow rig (Webb et al. 2011). Moreover, a longitudinal wave cut method was used to directly evaluate wave resistance (Eggers 1955). The two conditions tested were simulated using the open-source Computational Fluid Dynamics (CFD) code Open FOAM (Open FOAM® (2013)). The body geometry is a generic human form, morphed into the correct attitude and depth using the above- and under-water video footage recorded during the experiment. 3D Unsteady Reynolds-Averaged Navier-Stokes (URANS) simulations were performed using the Volume of Fluid (VOF) method to solve the air-water interface. A similar numerical technique was used by Banks (2013a) to assess the passive resistance of a swimmer. Two cases were simulated and the error in total drag compared to the experimental data was found to be 1% and 22% respectively. In this paper, the resistance components over a swimmer's typical range of speeds are investigated and compared with the experimental data.